Pengaruh Bimbingan Karir, Motivasi Memasuki Dunia Kerja dan Disiplin Belajar terhadap Kesiapan Kerja (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the effect of career guidance, motivation to enter the world of work and learning discipline on the work readiness of class XI students of the Office Administration Department at SMK Negeri 1 Karanganyar, Kebumen Regency for the 2017/2018 Academic Year. The population in this study were all students of class XI, Department of Office Administration, Academic Year 2017/2018 at SMK Negeri 1 Karanganyar, Kebumen Regency, totaling 107. The population was 107 people and the sample used a saturated sample. The method of data collection was done by questionnaire. The method of data analysis in this study used multiple regression analysis and descriptive percentage analysis. The results showed: 1) there was a simultaneous positive influence of career guidance, motivation to enter the world of work, and learning discipline on the work readiness of class XI students of the Office Administration Department at SMK Negeri 1 Karanganyar, Kebumen Regency by 69.8%, .